Estabilização de solos com o uso de resíduos cerâmicos da construção civil - Otubo, Aline Tiemi Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Given the changes that the planet is going through, today much of what is used is incorrectly discarded and could be reused. An example of this is construction and demolition waste (CDW), in particular ceramic aggregate, which is commonly descarded in landfills, but which can gain new characteristics in develpment of alternative materials. This work has as demonstrated the possibility of using ceramic aggregate in soil granulometric stabilization in order to generate high quality mixtures to be used in several layers of the road pavement. For this, four (4) diferente mass percentages (65%, 70%, 75%, 80%) of ceramic waste were emitted according to compaction and expansion tests. The results showed a significant increase in CBR with the addition of ceramic waste, for all studied proportions, compared to soil in nature, proving that the waste can be used in pavement of a road structure.

Diante das mudanças que o planeta passa, hoje muito do que é utilizado é descartado de maneira incorreta e poderia ser reutilizado. Um exemplo disso são os resíduos de construção e demolição (RCD), em específico o agregado cerâmico, o qual acaba comumente sendo descartado em aterros, mas que pode ganhar novas funcionalidades no desenvolvimento de materiais alternativos. Este trabalho tem como finalidade demonstrar a possibilidade de uso do agregado cerâmico em estabilização granulométrica de solo a fim de gerar misturas de elevada qualidade para serem utilizadas em diversas camadas do pavimento rodoviário. Para isso, quatro (4) diferentes percentuais mássicos (65%, 70%, 75%, 80%) de resíduo cerâmico foram avaliados segundo ensaios de compactação e expansão. Os resultados demonstraram aumento significativo do CBR com adição de resíduo cerâmico, para todas as proporções estudadas, comparado ao do solo in natura, comprovando que tal resíduo pode ser aproveitado em pavimento de estrutura rodoviária.
Soil stabilization with the use of ceramic waste from civil construction
Keywords: Ceramic aggregate; Granulometric stabilization; California Bearing Ratio (CBR); Paving; Civil construction waste; Agregado cerâmico; Estabilização granulométrica; Índice de Suporte Califórnia (CBR); Pavimentação; Resíduos de construção civil